The impact of privatisation of support service: an assesment by staff in three Hospitals in Kedah, 1998 - Azizah Ab. Manan,; Syed Mohamed Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study using qualitative and quantitative method at three government hospitals in Kedah to study the impact of privatisation of Support services in the hospital on hospital opemtional cost, quality of the services provided and also the impact on the hospital staff work load after privatisation. The assessment of quality and effect on work load is from staff perspective through self administered questionaire, while cost analysis is carried out using semistructured questionaire. The qualitative method involved in-depth interviews with the Zone Manager and Manager in three hospitals. Three services that involved in the studies are cleansing services, clinical waste management services and linen & laundry services. The result of cost analysis studies showed hospital operational cost is increased in all three hospitals. Cost in Hospital Jitra increased by 11.3% , Hospital Alor Setar by 13.8% and Hospital Kulim by 27.5%. Quality of the services provided were found to be in high quality. 57% of respondent give cleansing services as high quality, 81 % for clinical waste management services and 61.9% for linen & laundry services. Type ofhospital found to have significant relationship with quality assessment of cleansing services which respondent from bigger hospital give the lowest quality for cleansing services. Educational level were found to be influenced the assessment of quality of clinical waste management which staff with lower educational level give lower assessment to its quality. While place of work were found to influence the assessment of staff for the three services. Respondent from limited visitor ward's found to give higher assessment on quality of the three services. Assessment of staff work load were found to be increased in Hospital Alor Setar by 52.2% of respondent. While 65.2% of respondent from Hospital Jitra found work load to be reduced after privatization and 58.3% of respondent from Hospital Kulim also found their work load to be reduced after privatisation. Poor monitoring of the services and lack of staff are the main factors that lead to increased workload of hospital staff after privatisation.